How Do Self-Efficacy and Social Support Help International Students in Denmark Manage Stress and Foster Creativity? - Yusriani, Sri; Utomo, Kabul Wahyu; Patiro, Shine Pintor Siolemba; Hendrian, Hendrian (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
The study examined the dynamic interactions between challenge stressors, social support, self-efficacy, and creativity among international students in Denmark, a population that is vulnerable to academic and work stress. This research aims to understand how protective factors can mitigate stress and drive innovation in a complex global education environment. Using a quantitative approach, data were collected through a survey of more than 400 international students at Danish higher education institutions. The data were analyzed using Structural Equation Modeling (SEM) to test hypothetical relationships. Key findings suggest that stressors, challenges, and social support significantly improve self-efficacy. Furthermore, self-efficacy, challenge stressors, and social support directly contribute positively to creativity. Crucially, self-efficacy has been shown to mediate the relationship between challenge stressors and creativity, as well as between social support and creativity. These results underscore the importance of self-efficacy as a key mechanism that converts pressure and support into creative outcomes. The theoretical implication is the integration of psychological constructs in education management. At the same time, these findings suggest strategies for universities to create an environment that supports student well-being and creativity.